Role of physico-morphic and biochemical characters of different okra genotypes in relation to population of okra shoot and fruit borer, Earias vittella (Noctuidae: Lepidoptera) - HALDER, JAYDEEP; SANWAL, S K; RAI, AJEET KUMAR; RAI, A B; SINGH, B; SINGH, B K (The Indian Journal of Agricultural Sciences, 2015)
Ten promising genotypes of okra were field screened under natural infestation of shoot and fruit borer, Earias vittella Fabricius to assess its reaction. Ten biophysical parameters, viz. trichomes, fruit length, fruit width, fruit weight, fruit angle, total number of fruits and branches, leaf length, plant height, stem diameter and biochemical parameters like total phenol and anthocyanin content of fruits were studied in relation to the expression of varietal reaction towards shoot and fruit borer. It was observed that highly susceptible genotype SB 8 had relatively lower number of trichomes (24) as compared to tolerant genotype SB 6 which had 51.8 trichomes/cm2. Fruit length, width and fruit weight showed a positive correlation (r value = 0.376, 0.034, 0.026, respectively) with borer incidence. Susceptible genotype SB 8 possessed lower fruit angle (23.4°) and stem thickness (1.17 cm) as compared to tolerant genotype SB 6 (26.4° and 1.28 cm, respectively). Similarly, higher number of total leaves (38.8), fruits (15.75) and branches (3.6) per plant were also recorded from SB 8 as compared to other tolerant lines (SB 6, VROR 160, SB 10). Amongst the biochemical parameters, total phenol and anthocyanin showed negative correlation with the borer incidence. Free-choice arena and ovipostional tests also confirmed that highest larval orientation and egg laying were in susceptible genotype SB 8 (53.3 and 19.7%, respectively) than the other tolerant genotypes.